Penerapan model Group Investigation (GI) dalam pembelajaran analisis kasus pelanggaran Undang-Undang ITE - Elizamiharti Elizamiharti; Restyaliza Dhini Hary; Muhammad Reza Hasibuan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2019)
This study aims to determine the effect of applying the Group Investi-gation (GI) model in learning to analyze cases of violations of the ITE Law at the Professional Ethics Course at STMIK Indonesia Padang. This type of research is quantitative research with descriptive analytical methods. The type of research design used is a pre-experimental design with pre-test and post-test designs. The data in this study are scores obtained by students in learning to analyze cases of violations of ITE law in the Professional Ethics Course at STMIK Indonesia Padang from the results of tests before and after using the Group Investiation learning model. The results of these tests were compared using the t-test formula to determine whether or not the effect occurred. The results of this study indicate that the GI model can improve the ability of students to analyze cases of violations of ITE law in the Professional Ethics Course at STMIK Indonesia Padang.